Pengaruh Motivasi Kerja Dan Promosi Jabatan Terhadap Semangat Kerja Pegawai Pada Bagian Kesejahteraan Rakyat Sekretariat Daerah Kabupaten Malang - Wahyudi, Eko Juni; Astuti, Hastirin Widi; Sudarjo, Sudarjo; Wahid, Moehammad Nasri Abdoel; Djoewita, Djoewita (Universitas Pahlawan Tuanku Tambusai, 2024)
The aim of this study was to identify and analyze the influence of work motivation and position promotion on the employee's work enthusiasm in the People's Welfare Section of the Regional Secretariat of Malang Regency. This study used the explanatory research method with a sample of 30 respondents. Analysis techniques included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. Results suggest the work motivation variable has a partially significant effect on work enthusiasm as seen from the value of tcount > ttable (3.273 > 2.052). The position promotion variable also has a partially significant effect on work enthusiasm as seen from the value of tcount > ttable or (2.144 > 2.052). Furthermore, the variables of work motivation and position promotion simultaneously have a significant effect on work enthusiasm; this can be seen from the value of Fcount > Ftable or 25.521 > 3.34. The work motivation variable has a dominant influence on work enthusiasm because of the regression coefficient of the independent variable work motivation (X1) (0.476) > job promotion (X2) (0.400).